Juvenile psammomatoid ossifying fibroma with skull base and orbital wall invasion: a rare case report* - Ünsal, Özlem; Soytaş, Pınar; Kabukçuoğlu, Fevziye; Uslu Çoşkun, Berna (ENT Updates, 2017)
Juvenile ossifying fibroma is an uncommon, benign, fibro-osseous neoplasm with aggressive local growth. This tumor is distinguished from other fibro-osseous lesions especially by its age of onset, aggressive behavior, and clinical presentation. Two microscopic types have been described: trabecular and psammomatoid variants. In this case report, we presented a young male patient with juvenile psammomatoid ossifying fibroma involving the sinonasal region, skull base and the orbit, which was treated with endoscopic surgery.